Immobilization of conidiobolus coronatus alkaline protease on waste fungal biomass - Shankar, Shiv; Laxman, Ryali Seeta (Environmental Engineering and Management Journal, 2011)
Alkaline protease from Conidiobolus coronatus which is optimally active at pH 10 and 40 degrees C finds application in leather and detergent industries as well as for recovery of silver from waste photographic films. The protease was immobilized in Ca-alginate, polyacrylamide gel and alkali treated waste fungal biomass (ATWFB). ATWFB was found to be most suitable among the matrices tested. Glutaraldehyde marginally increased the binding to ATWFB. Binding of protease to ATWFB seems to be through adsorption as confirmed by FTIR spectra. Though temperature optima of free and immobilized proteases were identical, optimum pH of the immobilized enzyme shifted to 11 from 10. Temperature stability of the protease increased after immobilization. Immobilized protease could be reused 3 times with marginal loss in activity.
Keywords: Alkaline Protease; Conidiobolus coronatus; fungal biomass; Immobilization

Purification and characterization of an alkaline protease by a new strain of Beauveria sp - Shankar, Shiv; Rao, Mala; Laxman, Ryali Seeta (Process Biochemistry, 2011)
A fungal culture isolated from animal dung was identified as a new strain of Beauveria sp MTCC 5184 based on 18S rDNA and ITS nucleotide sequence homology. The fungal isolate secretes alkaline protease active at pH 9 and 50 degrees C. The alkaline protease from Beauveria sp (BAP) was purified to homogeneity with 10.2-folds increase in specific activity and 38.6% recovery. The molecular mass and isoelectric point of the protease were found to be 29 kDa and 9.3, respectively. The N-terminal sequence of the BAP showed only partial homology with subtilisin like proteases from other fungi. The enzyme was stable up to 40 degrees C and pH 3-11. The protease was inhibited by Cd(2+), Hg(2+) and Mn(2+). The activity was totally lost in the presence of 1 mM PMSF suggesting it to be a serine protease. The protease showed maximum activity with casein followed by haemoglobin and BSA. The purified protease is able to separate the endothelial cells and can be used in animal cell culture. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Animal cell culture; Beauveria sp; Sequence homology

Subtilase from Beauveria sp.: conformational and functional investigation of unusual stability - Dalal, Sayli A.; More, Snehal V.; Shankar, Shiv; Laxman, Ryali Seeta; Gaikwad, Sushama M. (European Biophysics Journal With Biophysics Letters, 2014)
Retention of total activity of the subtilisin-like serine protease from Beauveria sp. MTCC 5184 (Bprot) in the vicinity of (1) 3 M GdnHCl for 12 h, (2) 50 % methanol and dimethyl sulfoxide each for 24 h, and (3) proteolytic enzymes (trypsin, chymotrypsin, and proteinase K) for 48 h led to expect the enzyme to be a kinetically stable protein. Also, the structure of the protein was stable at pH 2.0. Biophysical characterization and conformational transitions were monitored using steady-state and time-resolved fluorescence, FTIR, and CD spectroscopy. Single tryptophan in the protein exists as two conformers, in hydrophobic and polar environment. The secondary structure of Bprot was stable in 3 M GdnHCl as seen in far-UV CD spectra. The active fraction of Bprot obtained from size-exclusion chromatography in the presence of GdnHCl (1.0-3.0 M) eluted at reduced retention time. The peak area of inactive or denatured protein with the same retention time as that of native protein increased with increasing concentration of denaturant (1.0-4.0 M GdnHCl). However, the kinetics of GdnHCl-induced unfolding as studied from intrinsic fluorescence revealed k (unf) of native protein to be 5.407 x 10(-5) s(-1) and a half-life of 3.56 h. The enzyme is thermodynamically stable in spite of being resistant to the denaturant, which could be due to the effect of GdnHCl imparting rigidity to the active fraction and simultaneously unfolding the partially unfolded protein that exists in equilibrium with the folded active protein. Thermal and pH denaturation of Bprot exhibited interesting structural transitions.
Keywords: Beauveria; Chemical denaturation; Conformational transitions; Serine protease; Subtilase; Thermal denaturation; Thermodynamic stability

Biophysicochemical characterization of an alkaline protease from beauveria sp. MTCC 5184 with multiple applications - Shankar, Shiv; Laxman, Ryali Seeta (Applied Biochemistry and Biotechnology, 2015)
This study illustrates the biophysicochemical properties of an alkaline protease, BAP (Beauveria sp. alkaline protease) from Beauveria sp. MTCC 5184. This protease exhibited maximum activity at 50 degrees C, pH 9.0, and stability in a broad pH range, in the presence of organic solvents, denaturants, as well as detergents. Wash performance studies revealed that BAP was able to remove blood clots/stains from blood-soaked cloth. Peptide mass fingerprinting results demonstrated partial homology of BAP with subtilisin-like proteinase. BAP showed catalytic activity against natural as well as synthetic substrates. Active site characterization of BAP confirmed the involvement of serine, tryptophan, and aspartic acid in catalytic activity. Detailed kinetic and thermodynamic studies of BAP demonstrated that the activation energy (Ea) for casein hydrolysis was 82.55 kJ/M, the specificity constant (Kcat/K-m), and the values of Delta G (change in Gibbs free energy) decreased with increase in temperature, whereas Delta H (change in enthalapy) and Delta S (change in entropy) were constant. The results of the present study indicate that BAP has potential for applications as detergent additive, in peptide synthesis, and in basic research.
Keywords: Active site; Alkaline Protease; Beauveria sp; Organic solvent; Substrate kinetics

Charge-switchable gold nanoparticles for enhanced enzymatic thermostability - Shankar, Shiv; Soni, Sarvesh K.; Daima, Hemant K.; Selvakannan, P. R.; Khire, Jayant Malhar; Bhargava, Suresh Kumar; Bansal, Vipul (Physical Chemistry Chemical Physics, 2015)
This study illustrates a facile strategy for efficient immobilization of enzymes on a metal nanoparticle surface. The strategy proposed here enables the enzymatic activity to be retained while increasing the enzyme thermostability. It is demonstrated that the use of a zwitterionic amino acid tyrosine as a reducing and capping agent to synthesise gold nanoparticles allows efficient immobilization of phytase enzyme through charge-switchable electrostatic interactions. The detailed kinetic and thermodynamic studies reveal that the proposed enzyme immobilization strategy improves the overall quality of phytase by reducing the activation energy required for substrate hydrolysis and broadening the temperature window in which immobilized enzyme is able to operate. The outcomes of this study indicate that the underlying zwitterionic nature of 20 natural amino acids along with significant variability in their isoelectric points and hydropathy indices as well the ability of some of the amino acids to reduce metal ions is likely to offer significant opportunities for tailoring nano-bio interfaces in a rational manner for a range of biological applications.

Green synthesis of silver nanoribbons from waste X-ray films using alkaline protease - Shankar, Shiv; Prasad, R. G. S. V.; Selvakannan, P. R.; Jaiswal, Lily; Laxman, Ryali Seeta (Materials Express, 2015)
This work illustrates a facile approach to synthesize silver nanoribbons from waste X-ray films using alkaline protease from Beauveria sp. MTCC 5184 (BAP). The green synthesized nanoribbons have been characterized by UV-Vis spectroscopy, TEM, and FTIR. The UV-visible spectra gave maximum absorbance at 400 nm. TEM micrograph showed well-dispersed silver nanoribbons with an average length of 200-400 nm. FTIR result demonstrated the respective bands of the silver nanoribbons and proteins. XRD data revealed crystalline nature of silver nanoribbons dominated with (111) facets. In vitro antibacterial activity in terms of minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) showed 8/16 mu g/mL (MIC/MBC) against Staphylococcus aureus ATCC 29213 and 4/8 mu g/mL (MIC/MBC) against Escherichia coli ATCC 25922. The green synthesized silver nanoribbons showed excellent biocompatibility up to 40 mu g/mL concentrations on mouse fibroblast cell line (L929).
Keywords: Alkaline Protease; Characterization; Cytotoxicity; Silver Nanoribbons; Waste X-ray Film